SURVEY OF DENTAL STUDENTS’ SELF-PERCEIVED PRACTICE, ATTITUDE, AND KNOWLEDGE TOWARD EVIDENCE-BASED DENTISTRY IN INDONESIA - Baqir, Ahmad Haidar; Firman, Dani Rizali; Putri, Fidya Meditia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Currently, evidence-based dentistry (EBD) is considered as the “gold standard” in providing oral healthcare. EBD integrates the best scientific evidence with the dentist’s clinical expertise and patient’s value. The aim of this study was to assess dental students’ practice, attitude, and level of knowledge toward EBD in Indonesia.Methods: In this descriptive cross-sectional study, dental students in Indonesia who were at least in their third semester of the clinical program were asked to fill out an online questionnaire. Samples were obtained using the convenience sampling technique. The instruments used were the Indonesian version of Student Evidence-based Practice Questionnaire (S-EBPQ) and a set of sociodemographic questions. Descriptive analysis was conducted in this study.Results: Three hundred eighty-one dental students from 22 dental schools in Indonesia completed the questionnaire and met the criteria needed. The means score of practice, attitude, knowledge in retrieving & reviewing evidence, and knowledge in sharing & applying evidence were 5.02 ± 0.96, 5.75 ± 0.99, 4.86 ± 0.88, and 5.22 ± 0.87.Conclusion: Dental students in Indonesia believe that their level of knowledge and frequency in practicing steps in EBD were tolerable. They also showed a positive attitude toward the implementation of EBD in clinical practice.